Failures Monitoring in Refrigeration Equipment (2018)
The refrigerators are the responsible to assure the temperature and humidity conditions for perishable products stored in it. In this sense, it is necessary to guarantee its good performance at all times in order to preserve the products. In this article We propose a failures monitoring system for refrigeration equipment using Internet of Things (IoT) technologies. The aim of the solution is to manage preventive and corrective maintenance programs and, in this way, We look for assuring the conditions of the consigned products that are distributed along an entire country. We present the conceptualization, the design of the system and the results of the proof of concept. © 2018, Springer Nature Switzerland AG.